Strategi Pembelajaran Pendidikan Agama Islam Berbasis Literasi Digital di Madrasah Ibtidaiyah - Siregar, Andi Suhendra; Andriyana, Juli; Humairoh, Fauziah (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Islamic education in Madrasah Ibtidaiyah faces challenges in utilizing digital technology developments to improve the quality of learning. This study aims to explore the application of digital literacy-based PAI learning strategies at MIS Humayroh Labuhan Batu Utara and identify students' responses to the application of these strategies. The research method used was qualitative with a phenomenological approach. Data were collected through interviews, observations, and document analysis. The results of the study indicate that the use of digital media, such as videos, learning applications, and online-based teaching materials, can enhance students' understanding of Islamic religious education. Students feel more engaged and motivated in the learning process; however, challenges such as technical issues, internet connectivity, and device access remain obstacles. The implications of this study highlight the importance of developing digital literacy-based learning strategies that are accessible to all students, as well as attention to adequate infrastructure factors. This study is expected to contribute to the development of more effective religious education curriculum and methodology in Madrasah Ibtidaiyah.